Role of Case-Based Discussion as Workplace-Based Assessment Tool in Urology and General Surgery - Shahzadi, Shimee; Shah, Muhammad; Ali, Liaqat; Adeeb, Humera; Jamil, Brekhna (Journal of Gandhara Medical and Dental Science, 2024)
OBJECTIVES To determine the effectiveness of case-based discussion in terms of medical record-keeping, clinical reasoning, clinical judgment, and self-reflection in the management of patients. METHODOLOGY A multidisciplinary descriptive study was conducted in the Department of Urology Institute of Kidney Diseases, Hayatabad Medical Complex Peshawar, and Department of General Surgery, Hayatabad Medical Complex Peshawar, Pakistan, from January to December 2023. A total number of 20 postgraduate residents, ten from Urology and General Surgery, participated in the study with equal male and female participants. Case-based discussion (CBD) assessments focused on medical record-keeping, clinical Decision-making, clinical judgment, management, follow-up, and reflective writing. The data was collected on structured proforma and was analyzed on SPSS-25. RESULTS The total number of study participants was 20, and 410 Case-Based Discussion sessions were conducted. This constitutes an average of 4.8 assessments per week. Most encounters were related to medical clinical decisions and management. The case-based discussion showed significant improvement on the Likert scale of the supervisor’s rating, which extended over four quarters on all major parameters of formative assessment (p 0.001). The multimodal regression test showed significant enhancement in learning parameters on case-based discussions. R2=0.172 F ration=25.141 n=410 (p=0.001). There was no significant difference in the gender of residents as well as training specialty of residents of urology and general surgery (p >0.05). CONCLUSION A case-based discussion is an effective tool for formative assessment of Urology and General Surgery postgraduate residents.